Pengaruh Total Aktiva, Dana Pihak Ketiga, dan Ekuitas pada Pengungkapan Tanggung Jawab Sosial Bank Syariah di Indonesia - Bernad Hananto; Endri Endri; Saeful Anwar (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2019)
Abstract Economic actors have responsibility for profit, environment, and society. Previous research was conducted to develop the concept of Social Responsibility into an Islamic Social Responsibility (ISR). Sharia value was translated into the theme of the Islamic Social Responsibility. Total Assets, Third Party Funds and Equity in Sharia Banks are proxies from principals managed by management (agents). This study aims to reveal whether Total Assets, Third Party Funds and Equity affect disclosure of social responsibility with Islamic Social Responsibility approach to Islamic banks in Indonesia disclosed in the annual report of Islamic banks. The data used in this study was taken from the annual report of 9 Islamic banks from 2008-2016. The results of this study indicate that Total Assets, Third Party Funds and Equity, partially, affect the disclosure of Islamic Social Responsibility, and simultaneously, only Third Party Funds that influence the disclosure of Islamic Social Responsibility. The greater the Third Party Funds, the better the disclosure of Islamic Social Responsibility.